The blood mSEPT9 is capable of assessing the surgical therapeutic effect and the prognosis of colorectal cancer. (25th July 2018) - Song, Lele; Guo, Shaohua; Wang, Jiayu; Peng, Xiumei; Jia, Jia; Gong, Yuan; Yang, Bo; Xiao, Wenhua; Dong, Cheng; Liu, Hongyi; Li, Yuemin
Aim: To investigate the performance of methylated SEPT9 (mSEPT9) in assessing the surgical therapeutic effect and prognosis of colorectal cancer (CRC).Methods: Blood samples before surgery and 1 and 7 days after surgery were obtained from 120 CRC patients, and mSEPT9 and carcinoembryonic antigen (CEA) assays were performed.Results: The mean plasma mSEPT9 level showed 57.6-times and 131.1-times decrease 1 day and 7 days after surgery, respectively. In contrast, mean CEA levels showed 2.51-and 2.70-times decrease 1 and 7 days after surgery. 86.7% of patients can be assessed by mSEPT9 while 44.2% can be assessed by CEA. Positive mSEPT9 detection before surgery correlated with higher risk of death after surgery.Conclusion: mSEPT9 is effective for CRC postsurgical assessment and prognosis prediction.